Successful Management of Complex Intestinal Tuberculosis with Ileal Perforation: A Case Report - Maryella Ernestien Thioluna; Purwanta, Raymond Sebastian (HM Publisher, 2024)
Background: Intestinal tuberculosis (ITB) with ileal perforation represents a formidable challenge in the realm of extrapulmonary tuberculosis. This case report underscores the complexities inherent in managing such cases, highlighting the critical need for a multidisciplinary approach that integrates pharmacological and surgical interventions. Case presentation: A 57-year-old male presented with a history of both pulmonary and intestinal tuberculosis, complicated by ileal perforation. He had previously undergone a six-month course of anti-tuberculosis treatment and a laparotomy for ileal perforation repair. The patient's current presentation included abdominal pain, nausea, and vomiting, indicative of obstructive ileus. Diagnostic assessments revealed elevated inflammatory markers and imaging confirmed partial obstructive ileus and active pulmonary tuberculosis. The patient was managed with extended anti-tuberculosis therapy and intravenous antibiotics, resulting in significant clinical improvement and enhanced quality of life. Conclusion: This case report emphasizes the importance of early detection, comprehensive assessment, and individualized treatment plans in managing complex ITB cases. The successful outcome achieved in this case underscores the efficacy of a multidisciplinary approach that combines pharmacological and surgical interventions.